Do surgeries for varicose veins carry a risk of deep vein thrombosis? Endovenous laser ablation and conventional saphenectomy – a comparison - Zbigniew Krasiński (Pediatria i Medycyna Rodzinna, 2017)
Venous diseases, in particular varicose veins of the lower extremities, are one of the most common chronic diseases and a significant cause of morbidity in Europe and the USA. Varicose veins are considered a risk factor for deep vein thrombosis. Most patients with varicose veins have great saphenous vein ostial insufficiency and reflux of varying degrees. Standard treatment in these cases is high ligation and stripping of the great saphenous vein. This surgery, however, carries a risk of thrombotic complications. Minimally invasive procedures, which include endovenous laser ablation of the great saphenous vein, are the current world trends. This method is a relatively new treatment option for great saphenous vein reflux. The authors present the current state of knowledge on the risk of deep vein thrombosis after different surgical procedures for the treatment of varicose veins in the lower extremity. The literature analysis has led to a hypothesis that lower limb varicose vein surgeries that involve laser obliteration of the great or small saphenous veins carry a lower risk of deep vein thrombosis compared with conventional surgeries. Tumescent anaesthesia, short duration of the procedure and rapid return to physical activity may play a role in deep vein thrombosis prevention. The authors underline that thromboprophylaxis should be implemented irrespective of the method, using risk evaluation, e.g. based on the Caprini scale.